2022
DOI: 10.1021/acs.jpcc.2c02133
|View full text |Cite
|
Sign up to set email alerts
|

Methane Activation on Pt2+ Sites on Pt/TiO2 with Adsorbed Nitrate Species as Evidenced by In Situ FTIR Spectroscopy

Abstract: Identification of methane (CH 4 ) activation sites on solid catalysts in CH 4 oxidation is crucial to provide understanding for the conversion of CH 4 to valuable oxygenates and thus has been a subject of intensive research. It has been suggested in many experimental and theoretical studies that oxidized metal sites, i.e., cationic sites, are responsible for CH 4 activation. However, clear spectroscopic evidence for this has been lacking. Here, we show that CH 4 is activated on the cationic sites, which was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Based on the reactivity and spectroscopic results, previous findings, and literature information, ,,, a reaction scheme for the reaction of methane and NO is proposed (Scheme depicts the formation of HCN and CO 2 , and Figure S25 illustrates the formation of all of the observed products.) Nitric oxide first adsorbs molecularly and dissociatively on Pt centers to form adsorbed NO (NO ads ), N (N ads ), and O (O ads ) species, and CH 4 adsorbs dissociatively to form adsorbed CH 3 (CH 3ads ) and H (H ads ) species.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the reactivity and spectroscopic results, previous findings, and literature information, ,,, a reaction scheme for the reaction of methane and NO is proposed (Scheme depicts the formation of HCN and CO 2 , and Figure S25 illustrates the formation of all of the observed products.) Nitric oxide first adsorbs molecularly and dissociatively on Pt centers to form adsorbed NO (NO ads ), N (N ads ), and O (O ads ) species, and CH 4 adsorbs dissociatively to form adsorbed CH 3 (CH 3ads ) and H (H ads ) species.…”
Section: Resultsmentioning
confidence: 98%
“…The catalytic consequences of the electronic state of Pt have been reported for various reactions with contrasting effects. ,,, For methane oxidation reactions, experimental and computational studies ,, have reported that cationic Pt species are highly reactive for C–H bond activation due to weaker adsorption of H* (or −H) species , and a strong metal–carbon bond. , For Au–Pt systems, the inactivity of Au toward CH 4 has been ascribed to its relatively weak metal and carbon bond; however, density functional theory (DFT) calculations have indicated that the presence of Au and the formation of metal cationic species reduce bonding electrons in the C–H σ bond and increase antibonding electrons in the C–H σ* bond of CH 4 , leading to enhanced activity toward CH 4 activation …”
Section: Resultsmentioning
confidence: 99%
“…Methane and its products do not share the active sites in indirect oxidation. 10,57,68,[73][74][75] Hence, the methane conversion rate and selectivity of indirect oxidation are usually greater than those of direct oxidation. 20,76 The research focus on indirect oxidation of methane is rather limited compared to direct oxidation.…”
Section: Indirect Oxidationmentioning
confidence: 99%